Tunnel visions into the sea of uncertainty - Schwartz, Jonathan ([S.l.] : Interlock Media [production company] : California : The Vodeo Project [distributor])
This program combines both history and science of the largest waste disposal project in the world and it's risk and reliability
Executive producer, Richard Gonci ; writers, Larry Davey, Good Davis, Natalie Boutin
Narrator: Douglas J. Mac Pherson ; host: Sylvia Earle
Keywords: Water tunnels; Sewage disposal; Waste disposal in the ocean